Removal of Textile Dye, RBBR, via Decolorization by Trametes hirsuta AA-017 - Fina Amreta Laksmi; Eva Agustriana; Isa Nuryana; Rike Rachmayati; Urip Perwitasari; Rumaisha Rumaisha; Ade Andriani (Biosaintifika: Journal of Biology & Biology Education, 2021)
The use of synthetic dyes has an impact on the possibility of disposing such dyes into the environment. Fungal decolorization is one promising approach due to its capability to degrade dyes, thus, exploring fungi that can be applied in dye decolorization is essential. We investigated our potential strain of Trametes hirsuta to decolorize Remazol brilliant blue R (RBBR). The enzyme activity of laccase in various conditions was observed using Syringaldazine as a substrate, while fungal immobilization was conducted using calcium alginate as a solid support. The results indicated that CuSO4 was the best inducer for the decolorization process. The fungus was able to perform 79.5% of RBBR decolorization for 48 hours in the presence of CuSO4. Laccase was the prominent detected ligninolytic enzyme when decolorization was performed. The immobilized cells were able to decolorize 85% RBBR under 0.8 mM CuSO4 andused for 3 cycles of decolorization. This study reveals the potential of fungal usage in the form of the immobilized and free cell to overcome the persistence of dye pollutants problem, as it is considered an effective, economic and eco-friendly approach for RBBR dye decolorization. These strategies can be suggested to encourage ecologically sustainable development for bioremediation.